Predicting the Halal Food Consumption of Indonesian Moslem Students: an Application of Theory of Planned Behaviour - Helmyati, Siti; Siagian, Rahma Yuni; Nisa, Fatma Zuhrotun; Radhiya, Salima; Yuliati, Endri (Jurnal Gizi dan Pangan, 2019)
The study aimed to predict halal food consumption behavior among Moslem students in three different universities in Yogyakarta City. Determinants to explain the halal food consumption was developed based on theory of planned behavior. The research applied cross-sectional design with total respondents of 168 Moslems students from State University, Islamic University, and Catholic University in Yogyakarta. The score of attitude, knowledge, subjective norm, perceived behavioral control and halal food consumption behavior were collected through a questionnaire. The data was analysed using Kruskall-Wallis and Multiple Linear Regression test. The study found that the score of knowledge in Islamic State and State University were higher than in Catholic University (7.43 vs 7.29 vs 7.09). The highest score of attitude was 51.52 in State University compared to Islamic State University and Catholic University (49.8 vs 47.61). The highest score of subjective norm was also in State University with the score of 3.59 while the score of halal food consumption behaviour was higher in State and Islamic State University compared to Catholic University (9.18 vs 9.18 vs 7.89). From those categories, the score of all variables except for the knowledge was statistically different between the three universities (p<0.05). It was concluded that the behavior of halal food consumption among Moslem students in Yogyakarta City may be predicted from the knowledge, attitude, subjective norm, and perceived behavioral control. These findings help to explain why the Moslem students in Yogyakarta eat halal food. Further research is needed to determine whether there are factors affecting halal food consumption behavior and how to improve it.